Quando a vontade de comprar se torna incontrolável: um estudo a partir da personalidade e valores humanos - Estanislau, Andrezza Mangueira (2020)
The objective this dissertation is to test a mediation model, considering Human Values as a mediator of the relationship between Personality and Compulsive Buying (CB). For this, three studies were carried out: Study 1 aimed to adapt the Richmond Compulsive Buying Scale (RCBS) for the Northeast region of Brazil. Three hundred (300) university students participated, the majority from a private university (67%), female (71%), with an average age of 23.5 years (SD = 6.7). They answered the RCBS and a sociodemographic questionnaire. An Exploratory Factor Analysis was performed and the results suggested the unidimensional of the instrument, explaining 51.85% of the total variance and a favorable internal consistency (Cronbach's α = 0.86). The purpose of Study 2 was to test the structure found in Study 1. There was the participation of 279 university students, the majority from public university (54.1%), male (51.3%), with average age 23.1 years (SD = 4.74). The participants responded to the same instruments as in Study 1. A Confirmatory Factor Analysis was carried out and the results showed good quality indexes for RCBS adjustments, confirming its yours unifactorial structure. Study 3 intended to understand the relationship between Personality Traits, Valuation Subfunctions and Compulsive Buying (CB); to verify the predictive power of Personality Traits and Human Values in compulsive buying; and, finally, to test the mediation model. Three hundred and twenty-nine (329) university students participated, the majority from a private university (54.1%), male (51.7%), with an average age of 24.67 years (SD = 6.34), who responded to the same instruments of the Study 2, in addition to The Big Five Inventory and the Basic Values Questionnaire. The result of the correlations, followed by regressions and the mediation model, demonstrated the contribution of the Extroversion, Neuroticism traits and the Realization subfunction in explaining the Compulsive Buying Behavior. It is believed that this dissertation contributes to the Compulsive Buying literature and Social Psychology, especially in explaining Compulsive Buying Behavior from a psychological perspective, because most studies on this construct are constituted in the administration area, more specifically in marketing. Furthermore, by knowing the factors that can influence the purchase compulsive, can help both consumers and professionals who deal with this kind of issue.